ESTIMATION OF BRUGUIERA’S CARBON STOCK IN BERBAK AND SEMBILANG NATIONAL PARK BANYUASIN SOUTH SUMATERA - Sarno, Sarno; Ridho, Moh. Rasyid; Indriani, Dwi Puspa; Harmida, Harmida; Pancasari, Adelia Rizki (BIOVALENTIA: Biological Research Journal, 2020)
The potential for the carbon content of mangrove forests is four times greater than other forest, this important information needs to be measured to determine the value of carbon stocks at a given time and their changes. The research was done in November 2018-March 2019 in Berbak and Sembilang National Park, Banyuasin, South Sumatra, in each location three transect lines were determined perpendicular to the land as far as 100 m and made 5 plots of 10 x10 m with a distance between plots of 10 m on each transect. The aims are to determine species richness, biomass value, estimated stored carbon reserves, and CO2 uptake in Bruguiera spp. stands. Analysis of comparison of the results of data using descriptive statistical analysis. Based on the results of the study found 4 types of Bruguiera spp. that is Bruguiera cylindrica, Bruguiera parviflora, Bruguiera gymnorrhiza, and Bruguiera sexangula. The total value of the biomass of 410,01 ton/ha, carbon stocks estimation of 189,02 ton C/ha, and the CO2 uptake of 693,69 ton CO2/ha. The results of a statistic descriptive analysis of estimated carbon stocks and CO2 uptake, in Barong Kecil river where of the most areas has been deforested into ponds, have the lowest value than the other research locations like Solok Buntu and Bungin river, with sequential carbon values of 11,51 ton C/ha in Barong Kecil river, 227,66 ton C/ha in Bungin river, and 327,88 ton C/ha in Solok Buntu river, and CO2 uptake of 42,23 ton CO2/ha in Barong Kecil river, 835,52 ton CO2/ha in Bungin river, and 1.203,33 ton CO2/ha in Solok Buntu river.